Analysis of Waste Management in The Village of Disanah, District of Sreseh Sampang, Madura - Muchammad Zamzami Elamin; Kartika Nuril Ilmi; Tsimaratut Tahrirah; Yudhi Ahmad Zarnuzi; Yanuar Citra Suci; Dwi Ragil Rahmawati; Dimas Mahendra Dwi P.; Rizky Kusumaardhani; Rizqi Azizir Rohmawati; Pandhu Aji Bhagaskara; Ismi Fuatjia Nafisa (JURNAL KESEHATAN LINGKUNGAN, 2018)
Waste is something that is always present in our daily lives. All the activities will inevitably result in the waste and so is going on in the village of Disanah, District of Sreseh, Sampang. The problem of this research is the process of waste management, which can't be categorised as good because the process is done by discharge management is not in the appropriate place and dispose it using the combustion process. The purpose of this study was to determine the existing waste management system in the village of Disanah, District of Sreseh, Sampang. The method used on this research is a qualitative study design with observational descriptive. It conducted by field surveys, focus group discussions with participants, open interviews, and literature study. Participants used in this study is representative of the Environment Agency, the village head, village councils, youth clubs and organizations in the village. The study states that waste management still in the unfavorable category, this is due to many factors: the lack of land for the construction of temporary shelters, facilities and infrastructures are not good enough and the level of public awareness is still low about the importance to manage waste properly. The advice can be given is to socialize, to schedule regular cleanup to clean the village and create a budget for land acquisition, which will be used for temporary shelter.